Proteolysis targeting chimeras (PROTACs) are emerging therapeutics for hematologic malignancies - He, Yonghan (J Hematol Oncol, 2020)
Proteolysis targeting chimeras (PROTACs) are heterobifunctional small molecules that utilize the ubiquitin proteasome system (UPS) to degrade proteins of interest (POI). PROTACs are potentially superior to conventional small molecule inhibitors (SMIs) because of their unique mechanism of action (MOA, i.e., degrading POI in a sub-stoichiometric manner), ability to target “undruggable” and mutant proteins, and improved target selectivity. Therefore, PROTACs have become an emerging technology for the development of novel targeted anticancer therapeutics. In fact, some of these reported PROTACs exhibit unprecedented efficacy and specificity in degrading various oncogenic proteins and have advanced to various stages of preclinical and clinical development for the treatment of cancer and hematologic malignancy. In this review, we systematically summarize the known PROTACs that have the potential to be used to treat various hematologic malignancies and discuss strategies to improve the safety of PROTACs for clinical application. Particularly, we propose to use the latest human pan-tissue single-cell RNA sequencing data to identify hematopoietic cell type-specific/selective E3 ligases to generate tumor-specific/selective PROTACs. These PROTACs have the potential to become safer therapeutics for hematologic malignancies because they can overcome some of the on-target toxicities of SMIs and PROTACs.